Advancing environmental sustainability in German hospitals : challenges and practices : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies in Management at Massey University, Manawatū, New Zealand - Suessenguth, Nora Johanna (Massey University, 2024)
This study focuses on the German healthcare sector, more specifically on German hospitals. In Germany, the healthcare sector is responsible for 5.2% of the national greenhouse gas (GHG) emissions and therefore has a substantial impact on environmental sustainability. Despite growing awareness about the importance of minimising their environmental impact, this aspect is still often neglected. Limited pressure and support, limited financial means, the difference of priorities in the healthcare sector, such as high quality patient care, and lack of knowledge about environmental management in hospitals are known reasons for this. Despite these barriers, a few hospitals in Germany have been able to dedicate resources to address environmental sustainability. This study aims to provide practical insights for hospital management and enhance understanding of how hospitals in Germany can advance in environmental sustainability despite the multiple barriers they face. Three research questions are addressed: (1) What actions are hospitals taking to improve their environmental sustainability? (2) What challenges do hospitals face in implementing these actions? (3) What practices enable hospitals to overcome these challenges and advance in environmental sustainability? This study draws on three theoretical frameworks regarding governance, development, and organisational change. To analyse how hospitals can advance in environmental sustainability based on these frameworks, the adaptive capacity needs to be examined, which determines how well an organisation is able to respond to changes and implement change initiatives to progress towards sustainability. Therefore, change initiatives of hospitals are examined, as well as four dimensions shaping the implementation of these initiatives: strategy making, organising processes, management capabilities and relational assets, thereby highlighting the challenges of implementation. For this study, a multiple explanatory case study design was adopted. Data were collected via semi structured interviews with people in four German hospitals whose task is to address sustainability, and with one managing director of an overarching organisation, linking the healthcare sector to sustainability. Findings were identified via thematic analysis. Three domains, with eight themes and various subthemes, categories, and codes were identified. Domain 1 (sustainability actions) includes theme 1: change initiatives, domain 2 (challenges in implementation) includes themes 2–5: strategy making, organising processes, management capabilities, and relational assets, and domain 3 (enabling practices) includes themes 6–8: establishing structures, collaboration and knowledge sharing, and openness to alternative approaches. First, sustainability actions were identified. They include initiatives to reduce environmental impact, change behaviour, increase resilience, and assess the environmental impact. Then, several challenges in implementing initiatives were identified within the dimensions of strategy making, organising processes, management capabilities, and relational assets. They include lack of external pressure and support, lack of knowledge, time, and personnel, organisational complexity, lack of funding, difficulty to change behaviour, and the competition of environmental sustainability with hygiene and patient safety. Finally, enabling practices to overcome these challenges were also identified. They include establishing structures within hospitals, engaging in collaboration and knowledge sharing with external and internal stakeholders, and openness to alternative approaches. These practices were found to improve implementation of change initiatives, which could impact the adaptive capacity of a hospital, leading to them being able to advance in environmental sustainability.
Keywords: 350711 Organisational planning and management; 420306 Health care administration